Effects of albumin administration in serum liver enzymes of rats in the presence of extrahepatic biliary obstruction - Lessa,Jorge Fernando Rebouças (2011)
PURPOSE: To study the influence of albumin on changes of liver function in the extrahepatic biliary obstruction through an experimental model in rats. METHODS: Sixty rats were divided into four groups: Group C (Control): 6 animals. Group M (Fictitious Operation): 18 rats underwent laparotomy and handling of the bile ducts; Groups O (extrahepatic biliary obstruction) and A (Treated with 2% albumin): 18 animals in each group underwent ligation of the ductus liver; The animals in groups M, O and A were divided into three subgroups of 6 animals each to be killed in the 7, 14 and 21 days postoperative (POD). Blood was drawn for determination of total bilirubin (TB), indirect bilirubin (IB), direct bilirubin (DB), alkaline phosphatase (ALP), aspartate aminotransferase (AST) and alanine aminotransferase (ALT). RESULTS: On POD 7, BI levels were 4.5 mg / dl in group O and 2.1 mg / dl in group A (p = 0.025). On the 14th POD, the levels of PA were 1185.2 U / l in the group and O 458.3 U / l in group A (p = 0.004). ALT levels were 101.7 U / l in the group O and 75.7 U / l in group A (= 0.037). On POD 21, the levels of ALP were 1069.5 U / l in the group O and 468.3 U / l in group A (p = 0, 004). CONCLUSION: The administration of albumin reduced the serum levels of bilirubin in the 7th day of supplementation